PERBANYAKAN VEGETATIF SECARA CANGKOK PIPER MINIATUM BL. - Priyono, Sumarnie Hasto (Jurnal Teknologi Lingkungan, 2010)
Ninety percent from approximately 1200 plant species belonged to Piper genus(Piperaceae) have not been explorated their phytochemical potency and biological activities. Piper miniatum has beeing used traditionally in Papua as spices and tonic. However, the propagation effort has never been done yet so its population in nature is decresed gradually. Therefore, simple propagation is conducted that can be adopted by the local people in order to cultivate as well as to explore its potency as antibacterial agent. The propagation experiment was carried out using air layering method with variable treatment of internode maturity ( R1, R2, R3 ), growth medium (Selaginela sp.,Asplenium nidus root, compost) with completely randomized design with 10 replications.Air layering media using Asplenium nidus root of 18 weeks gave the best respon.Key words: Piper miniatum, Air layering.